Amphicutis stygobita, a new genus and new species of brittle star (Echinodermata: Ophiuroidea: Ophiurida: Amphilepididae) found in Bernier Cave, an anchialine cave on San Salvador Island, Bahamas - Pomory, Christopher M.; Carpenter, Jerry H.; Winter, John H. (Zootaxa, 2011)
Amphicutis stygobita is a new genus and new species of ophiuroid found in Bernier Cave, an anchialine cave on San Salvador Island, Bahamas. The species is small (disk diameter 3–4 mm) with short arms (2–2.5X disk diameter). Dorsal disk features include imbricated scales, and oval radial shields separated by a column of scales. Ventral disk features include imbricated scales, genital scales flat and thin, no bursal sacs, second tentacle pore of oral frame outside mouth slit, oral shields small ovals similar in appearance to disk scales, two to three oral papillae per jaw side with the proximal papillae usually in the infradental position, and ventral tooth at the apex of each jaw broadly rounded. The arms are the most distinctive feature. Dorsal arm plates are small diamond-oval shaped and separated from one another by a gap equal to the arm plate length. Ventral arm plates are small figure-8 shaped and separated from one another by a gap equal to the arm plate length. Lateral arm plates meet medially on dorsal and ventral sides and make up most of an arm segment. Each lateral arm plate bears two arm spines. Disk and arms are often formed by soft tissue outlining plates and scales, but lacking significant calcification. A raised skin persists after calcification, from which the genus name derives. The species is named for its aquatic cave-dwelling habit, apparently endemic to a single cave, and may be unique among ophiuroids in being restricted to a cave environment.